CHILDBIRTH PROCESS AND WOMEN’S REPRODUCTIVE HEALTH IN OBSTETRICS AND GYNECOLOGY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This scientific article examines the physiological foundations and stages of the childbirth process in obstetrics and gynecology, as well as the concept, challenges, and strategies for promoting women’s reproductive health. Proper management of the childbirth process is a critical factor in ensuring the health of both mother and child. Protecting reproductive health is also one of the essential conditions for the development of society.
Keywords: Obstetrics, gynecology, childbirth process, labor stages, reproductive health, maternal care, nursing care, pregnancy, postpartum period, emergency conditions.